Guruku Sayang, Guruku Berkembang - Muhammad In’am Esha; Kusumadyahdewi Kusumadyahdewi; Ahmad Abtokhi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
Early Childhood Education Development (or PAUD in Indonesian) is essential in today’s world. A participative action research (PAR) approach was one of the actions done to support the development. One important stage in PAR is the preliminary study stage. The focus of this research is to know how the preliminary study was done in the perspective of problem mapping. The data collection techniques are performed with observations, surveys, documents, and interviews. This research produces a problem mapping model that is important in determining the problem that is used as the main agenda of mentoring to fit the needs of assistance by community priorities. The problem mapping model includes several stages: problem surveying and capturing, problem displaying, problem valuing, problem clustering, and a stage to determines the main problem for the action plan or the completion process.